Pengembangan Kuliner Dari Digital Marketing Dengan Menggunakan Aplikasi Go-Jek - Devina, Devina; Josley, Edvan; Hadianto, Isabela; Hendri, Jhoni (National Conference for Community Service Project (NaCosPro), 2019)
Culinary business is one of the promising business, that is the reason why many people chose culinary business as a source of income or an additional income. This also happened in Tiban Lama, Sekupang, Batam. Not to mention that there are still many people who purposely go out to buy the food that they want like Nasi Padang. This has caused the consumers of Nasi Padang to decrease. Regarding this matter, we have discussed and found out the way to broaden the marketing other than through effective social media, and that is by registering the stall to an e-commerce platform like GO-JEK. After the owner had registered to this platform, the owner had confessed that their revenue has increased, and the other impact is that the income of GO-JEK driver who lives in Tiban Lama or based around Tiban Lama area.